IMPLEMENTASI KOMPILASI ALGORITMA KRIPTOGRAFI TRANSPOSISI COLUMNAR DAN RSA UNTUK PENGAMANAN PESAN RAHASIA - Yuza Reswan; ujang juhardi; Bobi Tri Yuliansyah (Universitas PGRI Semarang, 2018)
Data security is important in maintaining the confidentiality of certain data that can only be known by those who have rights. If the data transmission is done by using network, there is a big possibility the data to be known by unauthorized parties.The columnar transposition algorithm is one simple transposition password. Columnar transposition is one of the classic cryptographic algorithms. Columnar transposition is one part of the transposition cipher with cryptographic method where the message is written in a row from a specified length, and then the column per column is read again with a reading sequence based on a keyword. Series length is determined by the length of the keyword. The order of column readings is based on column order.RSA Algorithm is one of asymmetric cryptography, which is a type of cryptography that uses two different keys: public key and private key. Thus, there is one key, namely the public key, which can be sent through a free channel, without any particular security. In this case there are two keys arranged so that they have a relationship in modulo arithmetic equation. In this case, combining both columnar transposition algorithms and RSA algorithms allows security in the form of message data to be very effective for locking the data even better.Keywords: Cryptography, Columnar Transposition, RSA, Java